Comparison of Application Effects of Capillary Radiation Heat Pump and Electric Heating Wire in Greenhouse Seedling Cultivation - Qiu Tu; Lina Zhang; Linzhang Li; Chenmian Deng; Bingjun Wang; Binquan Gu; Zhengwu Dai (Agriculture, 2022)
Heat pumps with water as heat exchange medium applied in greenhouse heating have not been used for vegetable seedling cultivation. In this work, a multi-connected direct expansion capillary radiation heat pump (MDCRHP) was designed for vegetable seedling cultivation, and a closed local temperature control (CLTC) method was proposed to accurately control air and substrate temperatures in seedling beds, enhance the heating effect and reduce the equipment cost. The results show that the CLTC method can achieve good heating effect and quickly raise air/substrate temperature at a speed of 1 °C/min from 8 °C to about 20 °C within 12 min. The air and substrate temperature fields in the seedling beds were evenly distributed. The temperature differences at different horizontal positions and different heights were less than 1 °C, and the relative humidity was 100%, which is conducive to vegetable grafting seedling. It can be concluded from test results that the MDCRHP had strong adaptability for greenhouse heating and was obviously superior to the electric heating wire (EWH). The output capacity of the compressor can be controlled by adjusting the operation frequency to meet the temperature requirements at different stages of seedling cultivation. Under the conditions of similar external ambient temperature and heating effect in the seedling beds, the energy saving rate of the MDCRHP was 47–50.7% compared with the EWH. The cost of the MDCRHP is about 7.2% lower than that of the conventional heat pump. It takes 3–3.5 years to recover the equipment investment.